2007
DOI: 10.1021/ol063010z
|View full text |Cite
|
Sign up to set email alerts
|

Aldehyde-Selective Wacker Oxidation in a Thiyl-Mediated Vinyl Group Transfer Route to Daunosamine

Abstract: [reaction: see text] Asymmetric dihydroxylation, thiyl radical mediated transfer of a silicon-tethered vinyl group to a hydrazone and an unconventional aldehyde-selective Wacker oxidation are sequenced for an efficient synthesis of methyl N-trifluoroacetyl-L-daunosaminide in 32% overall yield from crotonaldehyde.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 19 publications
0
14
0
1
Order By: Relevance
“…[59] Freistad et al reported, in 2007, the application of this system in the oxidation of trifluoroacetimide-protected allylic amines bearing an adjacent acetonide functional group with good AM selectivity. [60] Stahl and co-workers have reported the amination of styrene derivatives with palladium(II) as catalyst and deprotonated oxazolidinone as the nucleophile under aerobic conditions. [18] It was noted that the regioselectivity was controlled by the binding of the Brønsted base to the catalyst.…”
Section: Other Ligandsmentioning
confidence: 99%
“…[59] Freistad et al reported, in 2007, the application of this system in the oxidation of trifluoroacetimide-protected allylic amines bearing an adjacent acetonide functional group with good AM selectivity. [60] Stahl and co-workers have reported the amination of styrene derivatives with palladium(II) as catalyst and deprotonated oxazolidinone as the nucleophile under aerobic conditions. [18] It was noted that the regioselectivity was controlled by the binding of the Brønsted base to the catalyst.…”
Section: Other Ligandsmentioning
confidence: 99%
“…264,265 The thiyl radical-mediated transfer of a vinylsilane group to N,Ndibenzylhydrazone (or related N,N-diphenylhydrazone) (Scheme 67) was skillfully used as one of the synthetic steps in an asymmetric synthesis of an aminosugar, L-daunosamine, derivative. 266 Addition of thiyl radical (generated from PhSH and AIBN) to the vinyl group in 357 generated an intermediate alkyl radical which underwent cyclization with the CdN bond of the hydrazone group. The one-pot treatment of the resulting intermediate with fluoride removed silicon and regenerated the vinyl group via elimination of benzenethiolate.…”
Section: Radical Addition Of Silicon-tethered Vinyl and Acetylene Groupsmentioning
confidence: 99%
“…The chemical preparation of allylic amines has traditionally attracted great attention, due to the presence of this motif in numerous biologically active and natural products . In addition, their versatility in chemical synthesis has been widely demonstrated by their multiple applications for the preparation of valuable nitrogen‐containing organic compounds .…”
Section: Introductionmentioning
confidence: 99%